(untitled) (Research, Society and Development, 2021)
Introduction: Over the years, the elderly’s functional capacity declines. Functional capacity is based on being able to carry out daily tasks in an autonomous way, so the inclusion of resistance physical exercises in the training of the elderly becomes important, aiming to analyze the effectiveness of multijoint or monojoint exercise in increasing functionality. Objective: To evaluate the influence of monojoint and multijoint resistance exercise in increasing the functional capacity of the elderly. Method: Integrative literature review carried out in the databases: PUBMED, LILACS and SCIELO, including original scientific articles, in Portuguese and English that dealt with resistance training, functional capacity, multijoint and monojoint exercise in the elderly. An efficiency coefficient was determined in each selected study. Results: Five articles were selected to compose the sample, three of which used multijoint exercises in greater proportion within their training protocols. Conclusion: Multijoint exercises seem to positively influence the functional capacity of the elderly to the detriment of monojoint exercises, however it was observed that the subject is incipient in the scientific literature.